Evaluating real world income distributions behind the veil of ignorance: How risk averse do you have to be to prefer Europe over the US? - Alfons J. Weichenrieder; Tasneem Zafar (Luxembourg Income Study (LIS), 2011)
The paper uses a veil of ignorance approach and income distribution data of developed countries to arrive at inequality corrected income rankings. While a risk neutral individual (based on year 2000 data) would have preferred to be born into the US rather than any European country in our sample except Luxembourg, a coefficient of relative risk aversion of 2 suffices to make several European countries look preferable. The paper also sheds light on the risk corrected average income on a gender basis and scans for times of diminished expectations, i.e. periods where the expected utility of being born into a country has reduced over time.
Keywords: D31; H23; 330; income distribution; veil of ignorance; cross country comparison; Einkommensverteilung; Verfassungsökonomik; Präferenztheorie; Risikoaversion; Vergleich; USA; Europa